Exploration of Company Performance, Firm Growth, Profit Growth, Intellectual Capital, and Tax Justice - Mohammad Chaidir; Grace Yulianti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research explores the interplay between corporate success, firm growth, profit growth, intellectual capital, and tax justice. The study aims to understand the factors contributing to company performance within this framework. Employing a qualitative approach, the research utilizes interviews and document analysis as primary data collection techniques. A purposive sampling method is employed to select participants from various industries, ensuring diverse perspectives. Data analysis involves thematic coding to identify patterns and themes. Preliminary findings suggest a complex relationship between intellectual capital, tax justice, and corporate success, with implications for firm growth and profit growth. The study provides insights into the intricate dynamics shaping contemporary corporate environments and underscores the importance of ethical considerations in achieving sustainable business outcomes.